Oil Price Fluctuation and Health Outcomes in an Oil Exporting Country: Evidence from Nigeria - Oduyemi, Gabriel; Owoeye, Taiwo (International Journal of Energy Economics and Policy, 2020)
In oil exporting countries, government finance is heavily dependent on oil revenue and this tends to be highly volatile. This creates instability in output, terms of trade and fiscal balances, and lowers long-run growth rates and ultimately, social spending resulting into poor human development indicators. In Nigeria, indices of human capital development are among the worst globally despite its position as the largest oil producer in Africa. Using time series data from 1980 to 2017, and the Vector Autoregressive Model (VAR) estimates, this paper investigated how fluctuations in oil price affect health outcomes in Nigeria. The main results indicate that oil price shocks are not detrimental to health outcomes. This reinforces the fact that oil price shocks are neither necessary nor sufficient to explain changes that happen in health outcomes in this country. It is the way the government spends its resource windfalls, and the way it adjusts spending during a downturn that is accountable for the poor health outcomes in the Nigerian economy. The study therefore suggests strategic policies that supports ï¬scal prudence, minimizes macroeconomic distortions and improve health outcomes. This should be backed by adequate institutional capacity. Keywords: Oil Price, Fluctuation, Health Outcomes, Human Capital. JEL Classifications: E32, E62, I15, Q32 DOI: https://doi.org/10.32479/ijeep.9266